Evaluations for Ascochyta resistance in Phaseolus coccineus germplasm collection at C.I.A.T. (Centro International de Agricultura Tropical, Cali, Colombia) - Schmit, Véronique; Baudoin, Jean-Pierre (1987)
Seed multiplication, agronomic evaluation, and identification of parental genotypes for interspecific hybridization with Phaseolus vulgaris constitute the main research activities carried out in the P. coccineus collection (around 1600 accessions) held by CIAT. In 1985, 3 Ascochyta screening trials with replicates were conducted in Popayan and Rionegro (Colombia). Expt. involved 43 and 16 introductions of P. coccineus subspecies polyanthus and coccineus, resp.; 2 susceptible P. vulgaris var., ICA-Llanogrande and G 6040, were used as controls. All the accessions of the polyanthus subspecies performed well with only mild symptoms, if any, on the leaves. The best performing accessions were G 35336 and G 35182 (Guatemala), G 3537 (Mexico), and G 35372 (Colombia). These accessions were included in 1986 as parental genotypes in a crossbreeding program with Andean and East African var. of P. vulgaris, using either coccineus or vulgaris cytoplasm. (CIAT)